Self-Efficacy In Patients With Hypertension - Wa Ode Sri Asnaniar; Ramla Tuanany; S Samsualam; Nur Wahyuni Munir (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2021)
Hypertension is a chronic disease and a serious health problem in various countries that require selfcare management. Dealing with hypertensive patients requires compliance with their self-care to improve health status. Research  aimed to  determine the relationship of self-efficacy and  blood pressure in patients with hypertension at Makassar Regional General Hospital. It used cross sectional study design. The technique of determining the sample by using a purposivel sampling technique with a sample size of 53 people. The relationship test was carried out using Chi-square test with significance level ? 0.05. The results of this study showed that there were 17 patients with good self-efficacy, of which 10 (58,8%) pre hypertension and 7 (41,2%) had high blood pressure. Whereas there were 36 patients whose self-efficacy was lacking, of which 6 (16,7%) had pre hypertension and 30 (83,3%) had high blood pressure. The results showed that there was relationship between  self-efficacy and blood pressure. in patients with hypertension at Makassar Regional General Hospital with a value of p=0,005. The conclusion in this study is that there is relationship between  self-efficacy and blood pressure in patients with hypertension at Makassar Regional General Hospital. For this reason, it is hoped that hypertension sufferers will be more positive thinking so that they are able to think that all diseases are not a burden but an encouragement to believe in themselves so that they can undergo good treatment.